THE DISTINCTION BETWEEN DIVINE SPEECH (KALĀM ILĀHĪ), REVELATION (WAḤY), AND RISĀLAH IN THE THOUGHT OF MANNA AL-QAṬṬĀN: A Study on the Essence, Position, and Authority of the Qur'ān: DISTINGSI KALAM ILAHI, WAHYU DAN RISĀLAH DALAM PEMIKIRAN MANNA AL-QATTĀN: Kajian atas Hakikat, Kedudukan, Otoritas Al-Qur’an - Azizah, Putri Azizah Rustan; Andi Miswar; Muhammad Hasan (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2026)
This article examines the distinction between revelation (waḥy), divine speech (kalām ilāhī), and risālah in the perspective of Manna al-Qattan, highlighting the problem of fragmented readings in Qur’anic studies. The separation of these three concepts often produces epistemological bias, leading to the reduction of the Qur’an’s authority. This study aims to reconstruct the structural relationship between revelation as a communicative mechanism, divine speech as the substance of truth, and risālah as its social manifestation within an integrated framework. This research employs a library-based method with a descriptive-analytical approach, drawing on classical and contemporary sources, with particular focus on Mabāḥith fī ‘Ulūm al-Qur’ān. The findings reveal that al-Qattan bridges revelation and divine speech through the concept of tanzīl, understood as the process by which transcendent divine speech becomes communicative revelation. The study argues that revelation, divine speech, and risālah form an inseparable system that cannot be adequately understood in isolation. Accordingly, the Qur’an is positioned as the concrete manifestation of divine speech with supreme authority. The contribution of this research lies in reconstructing an integrative conceptual framework within Qur’anic studies while challenging the prevailing fragmentary approaches that obscure the fundamental relationship between these key concepts.